2018
DOI: 10.21273/hortsci12588-17
|View full text |Cite
|
Sign up to set email alerts
|

Response of Young Pecan Trees to Repeated Applications of Indaziflam and Halosulfuron

Abstract: Pecan production in the southeastern United States has increased because of the worldwide demand for the nuts of this tree. Information about the effects of the residual herbicides indaziflam and halosulfuron on newly planted pecan trees was evaluated over time for 4 years on sandy loam soils. After winter pecan tree planting, multiple spring or autumn herbicide applications were applied to the same pecan trees in different experiments in consecutive years. Visual injury, height, and caliper diameter m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
2
5
0
1
Order By: Relevance
“…This indicates the crop safety if a POST application of indaziflam after an initial harvest is needed to extend residual weed control. This is similar to other crop scenarios where indaziflam has been applied as split applications during the season (Grey et al 2016(Grey et al , 2018. At harvest 3, 154 to 167 DAT, there were no differences in yield for any herbicide treatments for fresh-or dry-weight biomass.…”
Section: Harvest Datasupporting
confidence: 81%
“…This indicates the crop safety if a POST application of indaziflam after an initial harvest is needed to extend residual weed control. This is similar to other crop scenarios where indaziflam has been applied as split applications during the season (Grey et al 2016(Grey et al , 2018. At harvest 3, 154 to 167 DAT, there were no differences in yield for any herbicide treatments for fresh-or dry-weight biomass.…”
Section: Harvest Datasupporting
confidence: 81%
“…At the end of this greenhouse study, no phytotoxicity effects on young pecan trees were observed when indaziflam and its breakdown products where present in the soil. Similar results were reported by Grey et al (2018) after exposing young pecan trees to multiple applications of indaziflam. However, studies on the mobility, degradation, and toxicity of indaziflam and indaziflam breakdown products should be conducted under different scenarios because there is limited published information available.…”
Section: Sand (%)supporting
confidence: 88%
“…This was always transient and no longer noted 8 wk after treatment. Many reports of little to no visual injury have been made for indaziflam applied to perennial crops (Basinger et al 2019;González-Delgado et al 2017;Grey et al 2018Grey et al , 2016Hurdle et al 2019).…”
Section: Blueberrymentioning
confidence: 99%
“…As a PRE herbicide, it is used in numerous crop settings and has shown to be safe to perennial crops including grapes (Vitis vinifera L.; Basinger et al 2019), olive (Olea europaea L.; Grey et al 2016), pecan (Carya Illinoinensis Wangenh. ; Grey et al 2018), bermudagrass forage (Cynodon dactylon L.; Hurdle et al 2019), turf (McCullough et al 2013, and citrus (Jhala et al 2013). These studies indicate that indaziflam is safe to use in numerous crop settings, but minimal information exists for its use on blueberry and blackberry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation